PEMBUATAN KEJU NABATI DARI KEDELAI MENGGUNAKAN BAKTERI ASAM LAKTAT YANG DIISOLASI DARI DADIH - Khaswar Syamsu dan Kartika Elsahida (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
Cheese generally has limitations to be consumed by people with milk protein allergies and vegetarian. Besides the price is relatively expensive, the fat content of cheese is also high. Proteins in soybean may be an alternative to protein of milk in cheese making because it has a protein content of which is not much different as well as a low fat content. The use of lactic acid bacteria from dadih as probiotic bacteria with the addition of food additives should be made to improve the quality of non-dairy cheese. This study aimed to determine the formulation of non-dairy cheese made from soybeans with the right flavor concentration which is able to resemble the dairy cheese and to evaluate its characteristics. The design used was a completely randomized factorial design. The types of treatments given were the type of soy milk, percentage of inoculum, and concentration of flavor added. Types of soy milk used were a commercial soy milk powder and fresh soy milk with percentages of inoculum 5%, 10% , and 15% (v/v) as well as the addition of cheese flavor concentrations of 0.5%; 0.7% ; 0.9% ; 1.1%; and 1.3% (w/v). Data were analyzed by ANOVA followed by Duncan test if it showed significant differences. A Not A Test showed that the addition of cheese flavor 0.9% (w/v) and as much as 15% (w/v) the amount of inoculum in fresh soy milk produced not significantly different smells with commercial dairy cheese at 95% confidence level. Non-dairy cheese produced can be classified as a semi hard cheese and skim cheese as seen from MFFB (moisture fat free basis) and FDM (fat in dry matter). Characteristics of non-dairy cheese produced were the water content of 66.3%; ash content of 3.27%; protein content of 26.74%; and the fat content of 0.36%.Keywords :dadih,lactic acid bacteri, non-dairy cheese, soybean